Pengaruh Penggunaan Google Classroom dan Zoom Meeting Dalam Pembelajaran Pendidikan Jasmani Daring Terhadap Minat Belajar Siswa Kelas xi di SMK Wisudha Karya Kudus - Andre Febriansyah Putra Nugraha (Journal of Physical Activity and Sports (JPAS), 2020)
Andre Febriansyah Putra Nugraha, "The effect of using google classrooms and zoom meetings in online physical education learning on learning interest of class XI students at SMK Wisudha Karya Kudus", Health and Recreation Physical Education Study Program, Faculty of Social Sciences and Sports Education, PGRI University Semarang , 2020. The background of this study is the results of the daily test scores of physical education subjects for class XI students at SMK Wisudha Karya Kudus, there are two XI classes who get daily test scores below the minimum completeness criteria of 75, namely XI TITL 1 and XI TITL 2. The formulation of the research problem is which is better between the use of google classroom and zoom meeting in online physical education learning to increase student interest in class XI at SMK Wisudha Karya Kudus. The purpose of this study was to determine the comparison of the use of google classroom and zoom meeting in online physical education learning on the learning interest of class XI students at SMK Wisudha Karya Kudus. This research method uses quantitative research methods. This type of research used in this study is a quasi experimental design (quasi-experimental). In this study using a two group research design pre-test post-test design with purposive sampling technique. The use of google classroom learning media in online Physical Education lessons can increase the learning interest of class XI TITL 1 students an increase in learning interest by 14.26%, while in class XI TITL 2 students there is an increase in learning interest by 6.49%. While the use of zoom meeting learning media in online physical education lessons can increase student interest in learning class XI TITL 1, there is an increase in learning interest by 1.02%, while in class XI TITL 2 students there is an increase in interest in learning by 1.27%. The conclusion is that the increase in the results of interest in learning when using google classroom learning media is higher than the zoom meeting. Hopefully it will be able to increase student interest in learning and be useful for student motivation in learning physical education online during the Covid-19 pandemic.   Keywords: Google Classroom, Zoom Meeting, Student Interests. Andre Febriansyah Putra Nugraha, “Pengaruh penggunaan google classroom dan zoom meeting dalam pembelajaran pendidikan jasmani daring terhadap minat belajar siswa kelas XI di SMK Wisudha Karya Kudus”, Program Studi Pendidikan Jasmani Kesehatan dan Rekreasi, Fakultas Pendidikan Ilmu Pengetahuan Sosial dan Keolahragaan, Universitas PGRI Semarang, 2020. Latar belakang dari penelitian ini adalah hasil ulangan harian nilai mata pelajaran penjas siswa kelas XI di SMK Wisudha Karya Kudus ada dua kelas XI yang mendapatkan nilai ulangan harian dibawah kriteria ketuntasan minimal 75, yaitu XI TITL 1 dan XI TITL 2. Rumusan masalah penelitian ini yaitu manakah yang lebih baik antara penggunaan google classroom dan zoom meeting dalam pembelajaran penjas daring untuk meningkatkan minat belajar siswa kelas XI di SMK Wisudha Karya Kudus. Tujuan penelitian ini yaitu untuk mengetahui perbandingan penggunaan google classroom dan zoom meeting dalam pembelajaran penjas daring terhadap minat belajar siswa kelas XI di SMK Wisudha Karya Kudus. Metode penelitian ini menggunakan metode penelitian kuantitatif. Jenis penelitian yang digunakan pada penelitian ini adalah quasi eksperimental design (eksperimen semu). Pada penelitian ini menggunakan desain penelitian two group pre-test post-test design dengan teknik sampling purposive. Penggunaan media pembelajaran google classroom pada pelajaran penjas secara daring dapat meningkatkan minat belajar siswa kelas XI TITL 1 terjadi peningkatan minat belajar sebesar 14,26%, sedangkan pada siswa kelas XI TITL 2 terjadi peningkatan minat belajar sebesar 6,49%. Sedangkan penggunaan media pembelajaran zoom meeting pada pelajaran penjas secara daring dapat meningkatkan minat belajar siswa kelas XI TITL 1 terjadi peningkatan minat belajar sebesar 1,02%, sedangkan pada siswa kelas XI TITL 2 terjadi peningkatan minat belajar sebesar 1,27%. Kesimpulannya adalah bahwa peningkatan hasil minat belajar saat menggunakan media pembelajaran google classroom lebih tinggi daripada zoom Meeting. Semoga mampu meningkatkan minat belajar siswa dan bermanfaat untuk motivasi belajar siswa dalam pembelajaran penjas daring selama pandemi Covid-19.   Kata Kunci: Google Classroom, Zoom Meeting, Minat Siswa.